1975
DOI: 10.1530/jrf.0.0430453
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Follicular Fluid and Oestradiol on the Luteinization of Rat Granulosa Cells in Vitro

Abstract: Summary. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
5
0

Year Published

1976
1976
1996
1996

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…The small but not significant reduction of inhibition observed with the oestrogen-free follicular fluid may have been due to a slight inactivation of the treated follicular fluid. The oestrogens of follicular fluid strongly stimulate the secretion of proges¬ terone by rat granulosa cells in vitro, although they do not influence its inhibitory effect on morpho¬ logical luteinization of the cells (Bernard, 1975). This finding, and the data of the present study, lend support to the hypothesis that luteinization may involve regulation of at least two processes, namely progesterone synthesis and morphological changes.…”
supporting
confidence: 84%
See 4 more Smart Citations
“…The small but not significant reduction of inhibition observed with the oestrogen-free follicular fluid may have been due to a slight inactivation of the treated follicular fluid. The oestrogens of follicular fluid strongly stimulate the secretion of proges¬ terone by rat granulosa cells in vitro, although they do not influence its inhibitory effect on morpho¬ logical luteinization of the cells (Bernard, 1975). This finding, and the data of the present study, lend support to the hypothesis that luteinization may involve regulation of at least two processes, namely progesterone synthesis and morphological changes.…”
supporting
confidence: 84%
“…Bernard (1975) showed that pig follicular fluid prevents morphological differentiation of rat granulosa cells in vitro, but does not alter their progesterone secretion. To investigate further the presence and nature of a 'luteinization inhibiting factor' in follicular fluid we compared the incorporation of [3H]uridine into the total RNA by rat granulosa cells after incubation in either serum or bovine follicular fluid.…”
mentioning
confidence: 99%
See 3 more Smart Citations